Real-World Assessment of the Association Between PCSK9i Adherence and LDL Reduction and Variability in a Chinese Clinical Practice - Ye X; Zhang S; Zhong X; Li M; Liu M; Zhuang X; Liao X (Clinical Epidemiology)
Xiaomin Ye,1,2,* Shaozhao Zhang,1,2,* Xiangbin Zhong,1,2 Miaohong Li,1,2 Menghui Liu,1,2 Xiaodong Zhuang,1,2 Xinxue Liao1,2 1Cardiology Department, First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2NHC Key Laboratory of Assisted Circulation, Sun Yat-Sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinxue Liao, Cardiology Department, First Affiliated Hospital, Sun Yat-Sen University, 58 Zhongshan 2nd Road, Guangzhou, 510080, People’s Republic of China, Tel +86-13903063724, Fax +86-020-28823388, Email liaoxinx@mail.sysu.edu.cn Xiaodong Zhuang, Cardiology Department, First Affiliated Hospital, Sun Yat-Sen University, 58 Zhongshan 2nd Road, Guangzhou, 510080, People’s Republic of China, Tel +86-13760755035, Email zhuangxd3@mail.sysu.edu.cnBackground: Real-world evidence about adherence to proprotein convertase subtilisin/kexin type-9 inhibition (PCSK9i) is needed in Chinese population.Objective: We aimed to evaluate the adherence patterns using anti-PCSK9 monoclonal antibody in Chinese clinical practice and explored the association between adherence to PCSK9i and low-density lipoprotein cholesterol (LDL-C) reduction ratio and variability.Methods: A total of 5373 patients initiating PCSK9i in the First Affiliated Hospital of Sun Yat-sen University were included as sub-analysis of the RED-CARPET registry. Adherence to PCSK9i was measured by proportion of days covered (PDC), calculated for treatment covered days divided by 365 days during a one-year period. Reduction ratio (percentage points, range 0– 100) was calculated as the ratio of reduction degree (difference between baseline value and the lowest value) to the baseline value. LDL-C variability was measured as standard deviation of three LDL-C measurement 2 weeks after medication initiation. We used linear regression to measure the association between PCSK9i PDC and the reduction ratio and variability of LDL-C. PDC (range 0– 1) was scaled by 10 in the model.Results: At 12 months, the mean PDC was 0.09 ± 0.10. PCSK9i PDC was positively associated with LDL-C reduction ratio after adjustment for traditional risk factors (Adjusted β 4.05, 95% CI [2.61, 5.50]), p< 0.001), which means for every 0.1-unit increase in PDC, the LDL-C reduction ratio increases by 4.05 percentage points. PCSK9i PDC was negatively associated with LDL-C standard deviation after fully adjustment (Adjusted β − 0.042, 95% CI [− 0.066, − 0.018]), p=0.001). For every 0.1-unit increase in PDC, the LDL-C standard deviation decreased by 0.042 units, indicating improved lipid stability with higher adherence.Conclusion: The adherence to PCSK9i presented as a skewed distribution, most people only received one injection, which did not reach the ideal adherence goal. Unsatisfactory adherence to PCSK9i reduce the lipid-lowering effect of PCSK9i.Keywords: medicine adherence, visit-to-visit variability, LDL-C reduction